La disparition des Indiens de Copiapó : dynamiques historiques et vulnérabilités humaines en milieu désertique au Chili (1744-1810) - Enrique Cortés Larravide (L'Ordinaire des Amériques)
In the mid-18th century, a few years before the collapse of the Kingdom of Chile and the birth of the Chilean Republic, in a valley by the southern border of the most arid desert in the world (Atacama), the Copiapó river dried up. Mining and agricultural interests in the upper valley had monopolized its water resources, leaving the inhabitants of the lower valley with hardly any water. Among those were the San Fernando de Copiapó Indians, who belonged to a larger group which used to live in the whole valley. This article will study how the overexploitation of the river’s waters impacted the local native population of the valley, through a twofold reflection on the notion of vulnerability and the history of the Copiapó Indians. This case study is original as there are few works devoted to non-Western and pre-industrial populations who were colonized by European countries and who directly and tragically suffered from the excessive overuse of natural resources.